2017
DOI: 10.18632/oncotarget.15419
|View full text |Cite
|
Sign up to set email alerts
|

Opioids: Modulators of angiogenesis in wound healing and cancer

Abstract: Opioids are potent drugs that are widely used to control wound or cancer pain. Increasing evidence suggest that opioids mediate clinically relevant effects that go beyond their classical role as analgesics. Of note, opioids appear to modulate angiogenesis - a process that is critical in wound healing and cancer progression. In this review, we focus on pro- and anti-angiogenic facets of opioids that arise from the activation of individual opioid receptors and the usage of individual concentrations or applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 130 publications
0
42
0
Order By: Relevance
“…Moreover, impairment of angiogenesis with aging contributes to delayed wound healing. Healing of skin wounds is a process that involves aggregation of keratinocytes and fibroblasts through the formation of highly vascular granulation tissue ( 2 , 17 , 18 ). Many aspects of the healing process are influenced by aging, and it was reported that formation of benign granulomas is inhibited in aged mice along with a decrease of capillary density ( 2 ).…”
Section: Angiogenesis In the Elderlymentioning
confidence: 99%
“…Moreover, impairment of angiogenesis with aging contributes to delayed wound healing. Healing of skin wounds is a process that involves aggregation of keratinocytes and fibroblasts through the formation of highly vascular granulation tissue ( 2 , 17 , 18 ). Many aspects of the healing process are influenced by aging, and it was reported that formation of benign granulomas is inhibited in aged mice along with a decrease of capillary density ( 2 ).…”
Section: Angiogenesis In the Elderlymentioning
confidence: 99%
“…Opioids are often administrated concurrently with anticancer drugs to patients with advanced disease and exhibit potent analgesic effects without excessive adverse effects [3]. Apart from their analgesic effects, recent evidence suggest that opioids might influence cancer progression via mediating angiogenesis and/or biological activities of tumor cells [4]. Among the clinically used opioids, such as morphine, oxycodone and fentanyl, the role of morphine in cancer biology has been studied the most.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, stimulation of m-opioid receptors is known to activate anti-apoptotic and mitogenic signaling pathways, to support angiogenesis and to suppress tumor-fighting immune cells. 17,[50][51][52] Lack of Clinical Evidence for Antineoplastic…”
Section: Summary Of the Pharmacological Basis Of Antineoplastic Dl-mmentioning
confidence: 86%
“…Further stimulation of such mutated receptors (through, e.g ., d , l ‐methadone) could promote tumor growth. Finally, there is equally sound data showing proliferation‐promoting and tumor growth‐supporting effects of opioids. For instance, stimulation of µ‐opioid receptors is known to activate anti‐apoptotic and mitogenic signaling pathways, to support angiogenesis and to suppress tumor‐fighting immune cells …”
Section: Summary Of the Pharmacological Basis Of Antineoplastic Dl‐mmentioning
confidence: 99%